ITEMS OF ISLAMIC DECORATION IN DECORATIVE DESIGNING OF IRAQI ALKLABIAT (GOWN) CLOTHES: الهـــــام طــــاهـــــر حسيــــن (Al-Academy, 2016)
Designing women clothes is one of the application arts has rules and fundamentals and also laws connected the individual , and it is the whole thought and the decorative element for the cloth, in this way it highlighted the aesthetic and functional aspects which achieving the basic objective of existing the design, and the design has motives of designer chisel of the ability to deduct and device new systems and relations of his self sense of the components from which one could sustain the designing thought.Besides, the cultural and philosophy level to him which considered elements and motives , the researcher depending on them in designing women clothes, and the research problem is limited on the imposing the following question: Could the decorative ,plantation decorative engineering items be mobilized in the decorative designs for the Alklabiat (Gown) clothes ?And the research aims at detecting detecting decorative ,plant decorative engineering items and their role in decorating the designing Alklabiat (Gown) clothes also applying suggested designs in which decorative and the first category included / the decorative items with the decoration elements in designing Alklabiat (Gown) / 1-Details of Islamic decoration in the Abbasian age, 2-The decoration elements in designing Alklabiat (Gown) cloth,3-Decoration and its connection with designing fasions and the second category / diversity in designing clothes and its relation with the human body as for the third category which displays implementation of the designing designs and presenting designing, decorative suggestions then followed by the research results and lastly list of references and abstract in English language